The Demand Creation Effect on the Indonesian Manufacturing Industry - Sulistyaningsih, Lusi; Machmud, T.M. Zakir S. (Journal of Developing Economies, 2022)
This study analyzes the impact of Foreign Direct Investment that creates a demand creation effect on domestic companies in the Indonesian manufacturing industry in 2010-2015. This study uses Input and Output data for 2010 and Industri Besar Sedang data in 2010-2015, both of which come from the Badan Pusat Statistik. The Fixed Effects model came out as the best model because it reflected different firm characteristics. The study concludes that the larger the foreign presence and the firm's size in an industry, the more demand-creating effect it will create. However, FDI enters highly concentrated industries and industries with high levels of imports, which will negatively affect the demand creation effect.